Impact of vegetation type and pre-processing on product yields and properties following hydrothermal conversion of conservation biomass. (March 2021) - Corton, J.; Donnison, I.S.; Ross, A.B.; Lea-Langton, A.R.; Wachendorf, M.; Fraser, M.D.
Abstract: Changes in agricultural practices and land abandonment across less favoured areas have led to an increase in land management for nature conservation. Substantial areas of vegetation are cut annually for habitat management, but the conservation biomass generated is generally discarded. Samples of two types of conservation biomass harvested from marginal sites dominated by rushes ( Juncus spp) or bracken ( Pteridium aquilinum ) were washed and pressed to generate fluid and fibrous process streams using the Integrated Generation of Solid Fuel and Biogas from Biomass (IFBB) process. Previous work established the fluid from the IFBB process could be anaerobically digested to generate enough energy for the washing and pressing stages. The current study focussed on the fibrous process stream, subjecting material to hydrothermal conversion and investigated the extent to which i) vegetation type, ii) the impact of pre-treatment by hot water washing and pressing (partial demineralisation) and iii) hydrothermal conversion route (hydrothermal carbonisation or hydrothermal liquefaction) affected the yields, relative proportions, and characteristics of products generated. Feedstock source had substantially more effect on product chemistry than product yields. The most effective process route for combustion fuel production was based on hydrothermal carbonisation of pre-processed feedstock. However, if bio-oil production was to be the priority product in a biorefinery, then biomass pre-processing would not be required. Highlights: Biomass is generated during management of low input high diversity (LIHD) vegetation. LIHD biomass was subjected to hydrothermal carbonisation and liquefaction. Pre-processing had little impact on related product yields and composition. Vegetation type had a greater effect on product chemistry. Utilising this type of unwanted biomass supports ecosystem service delivery.